Patient-centeredness and psychometric properties of the Defense and Veterans Pain Rating Scale 2.0 (DVPRS) - Costantino, Ryan C; Gressler, Laura E; Highland, Krista B; Oehrlein, Elisabeth M; Villalonga-Olives, Ester; Perfetto, Eleanor M (Pain medicine (Malden, Mass.), 2024)
Objective This study aims to assess the patient-centeredness and psychometric properties of the Defense and Veterans Pain Rating Scale 2.0 (DVPRS) as a patient-reported outcome measure (PROM) for pain assessment in a military population. Design A critical evaluation of the DVPRS was conducted, considering its fit-for-purpose as a PROM and its patient-centeredness using the National Health Council’s Rubric to Capture the Patient Voice. Setting The study focused on the use of the DVPRS within the Department of Defense (DoD) and Veterans Health Administration (VA) healthcare settings. Subjects The DVPRS was evaluated based on published studies and information provided by measure developers. The assessment included content validity, reliability, construct validity, and ability to detect change. Patient-centeredness and patient engagement were assessed across multiple domains. Methods Two independent reviewers assessed the DVPRS using a tool/checklist/questionnaire, and any rating discrepancies were resolved through consensus. The assessment included an evaluation of psychometric properties and patient-centeredness based on established criteria. Results The DVPRS lacked sufficient evidence of content validity, with no patient involvement in its development. Construct validity was not assessed adequately, and confirmatory factor analysis was not performed. Patient-centeredness and patient engagement were also limited, with only a few domains showing meaningful evidence of patient partnership. Conclusions The DVPRS as a PROM for pain assessment in the military population falls short in terms of content validity, construct validity, and patient-centeredness. It requires further development and validation, including meaningful patient engagement, to meet current standards and best practices for PROMs.